Effects of calcium supplementation on bone density in healthy children: meta-analysis of randomised controlled trials. Issue 7572 (15th September 2006) - Winzenberg, Tania; Shaw, Kelly; Fryer, Jayne; Jones, Graeme
Abstract: Objectives To assess the effectiveness of calcium supplementation for improving bone mineral density in healthy children and to determine if any effect is modified by other factors and persists after supplementation stops. Design Meta-analysis. Data sources Electronic bibliographic databases, hand searching of conference proceedings, and contacting authors for unpublished data. Review methods We included randomised placebo controlled trials of calcium supplementation in healthy children that lasted at least three months and had bone outcomes measured after at least six months of follow-up. Two reviewers independently extracted data and assessed quality. Meta-analyses predominantly used fixed effects models with outcomes given as standardised mean differences. Results We included 19 studies involving 2859 children. Calcium supplementation had no effect on bone mineral density at the femoral neck or lumbar spine. There was a small effect on total body bone mineral content (standardised mean difference 0.14, 95% confidence interval 0.01 to 0.27) and upper limb bone mineral density (0.14, 0.04 to 0.24). This effect persisted after the end of supplementation only at the upper limb (0.14, 0.01 to 0.28). There was no evidence that sex, baseline calcium intake, pubertal stage, ethnicity, or level of physical activity modified the effect. Conclusions The small effect of calcium supplementation on bone mineral density in the upper limb is unlikely to reduce the risk of fracture, either in childhood or later life, to a degree of major public health importance.